Life from the fragments: Ambivalence, critique, and minoritarian affect. Issue 1 (March 2021) - Wilkinson, Eleanor; Lim, Jason
In this commentary, we respond to Ruez and Cockayne's 'Feeling Otherwise' and consider what is at stake in debates concerning the moods and modes of critique. There is a tendency in geographical work on affect to privilege affirmation, yet a key question remains as to who benefits from such moods of critique and the kinds of analysis that they afford. We argue that dominant theorisations of affirmation and negativity often elide uncomfortable discussions of power, domination, and violence. We offer a reading of the relations between affirmation and negativity through 'minoritarian affects' – a reading that arises in the midst of living through racial capitalism, coloniality, patriarchy, and heteronormativity and which builds an indeterminate future from the fragments of our lives and bodies.